Application of palm oil fuel ash (POFA) as a stabilizer in tropical peat soil - Lau, Lik Yun (2016)
Among the different types of soft soil, peat is considered to be the poorest foundation materials due to its natural properties of high water content, high compressibility and low bearing capacity. Moreover, peat soil is susceptible to instability such as slip failure and localized sinking. Peat soil causes cracking, settlements and break-up of pavements, railways, highways, embankments, roadways, building foundations, reservoir linings and sewer line. These entire problems can be solved by improving the engineering properties of peat to make them suitable for construction. Therefore, palm oil fuel ash (POFA) was introduced as a soil stabilizer to improve the peat. POFA is one of the agricultural waste from the palm oil production mills. POFA in both cost-effective and environmentally friendly ways has potential applications in soft soil stabilization. The main focus of the research was to investigate the effect of POFA on the compressibility of peat soil. In this research, the disturbed peat soil extracted from the Pekan, Pahang, Malaysia was mixed with the ultrafine POFA to prepare samples with different dosages range from 5% – 20% of the wet mass of peat soil. All the samples were water cured for 7 and 28 days respectively. After curing, consolidation of treated samples was investigated by standard oedometer consolidation test. The size of all samples was 50mm in diameter, and 20mm in height. Compression index, coefficient of consolidation, and coefficient of volume compressibility were obtained by standard oedometer consolidation test. The method used for sample preparation was aimed at simulating the field condition of the mass stabilization technique. Prior to the oedometer test, the engineering characteristics of Pekan peat were determined. These are the fundamental tests which are important to give a clear full description of Pekan peat. Based on the results obtained, it shows that the increase in POFA ratio led to considerable decreases in compression indices of the stabilized Pekan peat.